Information systems : 14th European, Mediterranean, and Middle Eastern Conference, EMCIS 2017, Coimbra, Portugal, September 7-8, 2017, Proceedings /: 14th European, Mediterranean, and Middle Eastern Conference, EMCIS 2017, Coimbra, Portugal, September 7-8, 2017, Proceedings. (2017) - Unknown
No abstract available